Selection of a dispersion medium for recycling plastic greases according to fire and explosion indicators - Grigorov, Andrey; Sytnik, Alexey; Ponomarenko, Natalia; Neustroieva, Gelena; Nahliuk, Mikhail (My University, 2020)
The article presents the results of determining fire and explosion hazard indicators for used lubricants, which are supposed to be used as a dispersion medium in the production of recycling plastic greases. Having determined the flash point of the oils, it is possible to calculate the values of the ignition temperature and self-ignition according to linear regression equations, with an error of up to 2 °C. The flash point can be a criterion when choosing raw materials and layout of the technological scheme for the production of recycling plastic greases.
Keywords: grease; used oil; flash point; ignition; self-ignition; boiling fractions; regeneration